Translocating Mycobacterium ulcerans: An experimental model - Hammoudi, Nassim (PLoS One, 2020)
Mycobacterium ulcerans is a non-tuberculous environmental mycobacterium responsible for extensive cutaneous and subcutaneous ulcers in mammals, known as Buruli ulcer in humans. M. ulcerans has seldom been detected in the faeces of mammals and has not been detected in human faeces. Nevertheless, the detection and isolation of M. ulcerans in animal faeces does not fit with the current epidemiological schemes for the disease. Here, using an experimental model in which rats were fed with 10(9) colony-forming units of M. ulcerans, we detected M. ulcerans DNA in the faeces of challenged rats for two weeks and along their digestive tract for 10 days. M. ulcerans DNA was further detected in the lymphatic system including in the cervical and axillary lymph nodes and the spleen, but not in any other tissue including healthy and broken skin, 10 days post-challenge. These observations indicate that in some herbivorous mammals, M. ulcerans contamination by the digestive route may precede translocation and limited contamination of the lymphatic tissues without systemic infection. These herbivorous mammals may be sources of M. ulcerans for exposed populations but are unlikely to be reservoirs for the pathogen.